Evaluating blood levels of neuron specific enolase, chromogranin A, and circulating tumor cells as Merkel cell carcinoma biomarkers - Gaiser, Maria; Hoffmann, Jochen; Brune, Maik; Enk, Alexander (OncoTarget, 2015)
https://doi.org/10.18632/oncotarget.4500 Maria Rita Gaiser, Kenneth Daily, Jochen Hoffmann, Maik Brune, Alexander Enk, Isaac Brownell